CLASSIFICATION OF THE POWERS OF THE HEAD OF STATE - Tebayev, Дидар Болатович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
In the article, the author examines the typology of powers of heads of state, the basis for the classification of powers, citing the opinions of foreign scientists. The analysis of scientific works shows the variety of types of grouping of powers of the head of state. The purpose of the scientific work is to identify problems in classifying the powers of the head of state on certain grounds and to develop proposals aimed at solving the identified problems. When writing the article, the author used a complex of general scientific and specific scientific methods of cognition. The author notes that most scientists adhere to the so-called classical approach when classifying powers, the basis of which is the sphere of activity of the head of state. At the same time, some note some features in the typology of the powers of the head of state. For example, it is proposed to distinguish one’s own powers (some suggest calling them traditional), powers according to branches of government, internal and external, according to the method of implementation. Most powers have overlap, which leads to some confusion when classifying them. In his work, the author draws attention to such a category as the so-called “hidden” and other powers. The threat of both hidden and other powers lies in the possible unconstitutional expansion of their scope, including through judicial practice (Resolutions of the Constitutional Court of the Republic of Kazakhstan). The author draws attention in detail to the author's classifications of the powers of the head of state. Some of them use bases that do not have a formal logical connection and have multiple intersections. Some classifications of non-CIS authors for the Republic of Kazakhstan are, in all likelihood, not relevant for systematizing the powers of the President. In conclusion, an assessment of the studied classifications of powers of heads of state is given and recommendations are given on the typology of powers of the President of the Republic of Kazakhstan.